Aplication SIMULATION OF THE APPLICATION OF THE GREEN PRODUCTIVITY METHOD TO INCREASE THE PRODUCTIVITY OF HYBRID DUCK FARMING : Case Study Of Fery Wahyudi’s Duck Farming Business - Kuncorosidi Kuncorosidi (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2025)
This study examines the implementation of the Green Productivity framework in a mixed duck-farming enterprise managed by Fery Wahyudi in Subang, West Java. The research integrates economic productivity analysis with an environmental impact assessment to derive three principal indicators, namely the Economic Indicator, the Environmental Index (EI), and the Green Productivity Index (GPI). These indicators serve as the basis for evaluating the sustainability performance of the farming system. The findings indicate that the economic productivity score reaches 1.317, while the EI is calculated at 250.27, resulting in a GPI value of 0.00526. Two improvement scenarios are assessed to enhance sustainability outcomes: (1) the application of EM4 for the fermentation of livestock waste and (2) the production of organic fertilizer as an added-value product. The first scenario leads to an 11.6% increase in the GPI and an 8.09% reduction in the EI, demonstrating measurable gains in both productivity and environmental performance. The second scenario contributes to product diversification, strengthens the enterprise’s green value proposition, and supports the development of environmentally responsible branding. Overall, the study demonstrates that the Green Productivity approach is both feasible and beneficial for small-scale livestock operations. The results provide evidence-based insights and practical recommendations that can support local farmers in improving operational efficiency while simultaneously advancing environmental stewardship.